Acute kidney injury predicts the risk of adverse cardio renal events and all cause death in southeast Asian people with type 2 diabetes - Janus Lee; Jian-Jun Liu; Sylvia Liu; Allen Liu; Huili Zheng; Clara Chan; Yi Ming Shao; Resham L Gurung; Keven Ang; Su Chi Lim (Scientific Reports)
Abstract Patients with diabetes are susceptible to acute kidney injury (AKI) as compared to counterparts without diabetes. However, data on the long-term clinical outcome of AKI specifically in people with diabetes are still scarce. We sought to study risk factors for and adverse cardio-renal outcomes of AKI in multi-ethnic Southeast Asian people with type 2 diabetes. 1684 participants with type 2 diabetes from a regional hospital were followed an average of 4.2 (SD 2.0) years. Risks for end stage kidney disease (ESKD), major adverse cardiovascular events (MACE) and all-cause death after AKI were assessed by survival analyses. 219 participants experienced at least one AKI episode. Age, cardiovascular disease history, minor ethnicity, diuretics usage, HbA1c, baseline eGFR and albuminuria independently predicted risk for AKI with good discrimination. Compared to those without AKI, participants with any AKI episode had a significantly high risk for ESKD, MACE and all-cause death after adjustment for multiple risk factors including baseline eGFR and albuminuria. Even AKI defined by a mild serum creatinine elevation (0.3 mg/dL) was independently associated with a significantly high risk for premature death. Therefore, individuals with diabetes and any episode of AKI deserve intensive surveillance for cardio-renal dysfunction.